DEVELOPMENT OF INTERACTIVE VIDEO MEDIA BASED ON DISCOVERY LEARNING MODEL ON FOOD DIGESTIVE SYSTEM CLASS XI TO INCREASE STUDENT LEARNING OUTCOMES - Sudaryanti, Sri; Yulianti, Dwi; Pramudiyanti, Pramudiyanti (Universitas PGRI Madiun, 2023)
The purpose of this study was to develop and describe interactive video media based on discovery learning models in the food digestive system of class XI to improve student learning outcomes that were valid, practical, and effective. The type of research used in this study is the ADDIE development model, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. The limited trial phase was carried out in class XII MIPA 4 and the field trial phase was carried out in class XI MIPA 1 SMA Negeri 5 Bandar Lampung. The results showed that the product of developing interactive video media based on the discovery learning model in the food digestive system of class XI got an average score of 90% (very valid), media experts 91% (very valid). For the practicality questionnaire, the average score for the limited test students' responses got an average score of 93.25% (very practical) and the field test student response questionnaires got an average score of 92.40% (very practical). At the field trial stage, the learning outcomes got an average score of 0.71% (very effective). It can be concluded that the development of interactive video media based on the discovery learning model on the food digestive system for class XI to improve student learning outcomes is feasible to use in learning.